Valuable Defermination of Student’s Group - Samoilov, O. A. (Psychological Prospects Journal, 2011)
Article is devoted to finding the value of integrity condition of the student group in the context of sociogenic change. The author examines the basic value preferences and their influence on the degree of importance of integrity in case of group students Azov State Technical University.